2022
DOI: 10.1021/acschemneuro.2c00342
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Phospho-Tau Aggregation-Based Biomarker Discovery for AD Diagnosis and Differentiation

Abstract: Tau aggregates are present in multiple neurodegenerative diseases known as "tauopathies," including Alzheimer's disease (AD), Pick's disease (PiD), progressive supranuclear palsy (PSP), and corticobasal degeneration (CBD). Such misfolded tau aggregates are therefore potential sources for tauopathy biomarker discovery. Using the tau antibody screening approach targeting high-molecular-weight misfolded tau aggregates, we tested several tau antibodies and a comprehensive set of site-specific phospho-tau (p-tau) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Skin homogenates from cadavers with AD (n=5), PSP (n=4), CBD (n=4), PiD (n=4) and NC (n=4) were examined by western blotting with antibodies directed against phosphorylated tau (Anti-pT231 and Anti-pS396). P-tau231 and p-tau396 epitopes were previously identified from a systematic p-tau antibody screening in differential detection with AD and control brains [51]. Both the pThr231 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin homogenates from cadavers with AD (n=5), PSP (n=4), CBD (n=4), PiD (n=4) and NC (n=4) were examined by western blotting with antibodies directed against phosphorylated tau (Anti-pT231 and Anti-pS396). P-tau231 and p-tau396 epitopes were previously identified from a systematic p-tau antibody screening in differential detection with AD and control brains [51]. Both the pThr231 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to find an appropriate tau substrate for setting up our seed-amplification assay of skin tau (sTau-SAA) with the ultrasensitive RT-QuIC technique, based on our recent finding with autopsy brain tissues from cadavers with AD and other non-AD tauopathies [53], we first examined 4 types of tau substrates including 2 full-length tau isoforms (2N3R/2N4R) and 2 truncated tau fragments consisting of 4RCF (cysteine-free, equivalent to K18CFh)/3RCF (equivalent to K19CFh) using autopsy skin samples from AD cadavers. 4RCF represents the core aggregation sequences of the 4R tau isoforms [51, 53]. Correspondingly, 3RCF fragment represents the core aggregation sequences of the 3R tau isoforms.…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis suggested that p-tau217 had better discriminative accuracy for MCI than p-tau181 and p-tau231 ( Chen et al, 2022 ). We recently showed that a new neuropathological biomarker p-tau198 had capability to diagnose MCI cohorts from cognitively normal subjects in brain tissues ( Wu et al, 2022a ). Therefore, it will be interesting in the future to evaluate these promising p-tau biomarkers or to develop novel p-tau biomarkers for plasma and CSF tests.…”
Section: Discussionmentioning
confidence: 99%
“…They found an intriguing new biomarker, p-tau 198, beneficial for spotting abnormal tau protein in the brain at the early stages of AD. 21 Early detection and effective AD treatment may be revolutionized by a simple, affordable, and accurate blood test for p-tau 198. According to a different study, tiny nucleotides that attach to mRNAs can be found in the blood and detect a cellular imbalance in the brain.…”
Section: Exploring Blood-based and Urine-based Biomarkers For Early D...mentioning
confidence: 99%